Experimental Study of Mixed Convection in an Enclosure with a Cold Movable Top Wall and Hot Bottom Wall - Yasin, Nabil J. Yasin J.; Alwan, Dhia Al-Deen H.; Abdulla, Ayad S. (Al-Khwarizmi Engineering Journal, 2017)
Mixed convection heat transfer to air inside an enclosure is investigated experimentally. The bottom wall of the enclosure is maintained at higher temperature than that of the top wall which keeps in oscillation motion, whereas the left and right walls are well insulated. The differential temperature of the bottom and top walls changed several times in order to accurately characterize the temperature distribution over a considerable range of Richardson number. Adjustable aspect ratio box was built as a test rig to determine the effects of Richardson number and aspect ratio on the flow behavior of the air inside the enclosure. The flow fields and the average Nusselt number profiles were presented in this work. The results show that, at a constant value of the Richardson number, average Nusselt number (Nuav.) increases with aspect ratio. Furthermore, as Richardson number decreases, the time period decreases with constant values of aspect ratio.